Credit Market Imbalances in Russia: Dynamics and Risks - A. Yu. Belyaninov; A. P. Garnov; D. G. Perepelitsa (Вестник Российского экономического университета имени Г. В. Плеханова)
Digital-marketing market is growing exponentially. There are a lot of services, platforms and technologies that are used for business promotion. While 10 years ago only Google and Facebook were available, today we can see thousands of various solutions. Analysts forecast transit of all industries to digital space. Changes in behavioral skills of customer finance services and growing competitive pressure on the part of start-ups ruin conventional business-models and induce us to develop new strategies. Therefore banks and other regulated finance intermediaries try, with due regard to their budgets, to master as quickly as possible innovations in the field of finance technologies and alter formats of client service. A typical feature of today’s society development is increasing innovation of all spheres of human activity. For example, now we can observe break-through innovation in technology, which changes not only technical and technological foundations of economy but drastically influence different processes in the social sphere. Researching credit strategies within the frames of economic behavior of the population is connected mainly with studying the grounds, key trends and consequences of individuals’ operations on finance service market. The article investigates specific features of Russian citizens’ behavior in the segment of mortgage crediting and auto-crediting, analyzes figures of banks in crediting individuals and shows risks of repayment delay. The authors systematized key concepts of regulating credit and finance markets, which is needed for the process of designing the effective regulatory model that takes into account specific features of markets. The findings of the research can be used in assessing the efficiency and improvements in international coordination of national regulators on finance markets.